Evaluation of evaporation trap on the calibration of piston pipettes within nominal values under or equal to 100 μl - Méndez Arias, Johanna (2017)
This paper aims to demonstrate the importance of using evaporation trap during piston pipette calibration, specifically at microliter levels (μL). Calibrations were performed in a laboratory pipette using the gravimeter method with evaporation trap, and without trap or any correction by evaporation. 10 repetitions were performed at three different points and the values provided by the calibration certificate of the analyzed pipette were compared to a reference value determined by the National Metrology Laboratory (LACOMET).